Avaliação da resposta da frequência cardíaca, da pressão arterial e da variabilidade da frequência cardíaca à contração dos músculos do assoalho pélvico - Bastos, Alana Maria Ferreira Guimarães (Universidade Federal de São Carlos, 2014)
To prevent and treat pelvic floor muscle (PFM) dysfunctions, level A of evidence proposes isometric contractions to strengthen these muscles. In literature, there are studies regarding the cardiovascular effects of isometric exercises and the cardiac autonomic regulation in response to these exercises. However, currently there are no studies regarding the cardiovascular response to PFM exercises and the effects of these responses to sympathetic and parasympathetic cardiac modulations. Therefore, the objective of this dissertation was to analyze heart rate (HR) response to a protocol of PFM contractions and the acute effect of the PFM contractions in blood pressure (BP) and sympathetic and parasympathetic cardiac modulations responses and compare these variables to rest conditions before and after the PFM contractions. We evaluated eutrophic women aged between 18 and 80 years, divided in groups according to age. They underwent two protocols; each one containing a series of PFM contractions with monitoring of the PFM contraction pressure, HR, BP and R-R intervals. Both series contained 10 PFM contractions, one series contained contractions lasting 5 seconds with 5 seconds of rest between each contraction and the other series contained contractions lasting 10 seconds with 10 seconds of rest between each contraction. We observed an increase in HR during PFM contractions and an increase in systolic BP immediately after the contractions in the evaluated groups. Regarding the cardiac autonomic regulation, we performed the time domain (RMSSD and SDNN indexes) and frequency domain (low and high frequency spectral components in absolute values) analysis. We observed increase in SDNN and RMSSD indexes during PFM contractions; after frequency domain analysis we observed predominance of vagal modulation in the group containing young women after the series of PFM contractions with 10 seconds and the group consisting of adult and elderly women showed a higher prevalence of sympathetic modulation after series of PFM contraction lasting 5 seconds. The observed variables were within the normal values and returned to basal values as soon as the contractions ended. In conclusion, the proposed protocol of PFM contractions might not represent a cardiovascular risk for healthy women. Moreover, the applied protocol did not changed positively or negatively the cardiac autonomic modulation.
Keywords: Fisioterapia; Contração isométrica; Sistema nervoso autonômico; Sistema cardiovascular; Controle autonômico; Autonomic control; Cardiovascular system; Isometric contraction; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL